Drifting apart: Family law matters and the ‘Politics of Brexit’ - Davies, Cleo (Border Crossing, 2025)
The UK and the EU have no formal agreement on civil justice cooperation on family matters despite both sides agreeing on the need to cooperate post-Brexit during the negotiations. Not only does the Trade and Cooperation Agreement (TCA) make no provisions on cross-border family law matters, but the EU also rejected the UK’s request to accede to the Lugano Convention, which would have largely replicated provisions that existed when the UK was a member state. Instead, uncertainty means UK and EU citizens could face delays and increases in legal costs for cross-border cases. This paper examines how the political dynamics of EU exit hinder cooperation on family law matters because the principle of reciprocity is trumped by political considerations The paper also contextualises post-Brexit cooperation by highlighting how the ‘politics of Brexit’ dovetail with internal EU sensitivities on the EU’s external action in civil justice cooperation in family matters.